Antihiperglicemic activity of ethanol extract of Jumpai batang (Glinus oppositifolius (l.) Aug. Dc.) in overloaded sucrose-swiss strain male mice - Amin, Astuti; Hendra, Wahyu; Awaluddin, Akbar (Annals of Mechnikov's Institute, 2023)
Background: Diabetes mellitus is a metabolic disorder associated with relative or absolute insulin deficiency or resistance, characterized by hyperglycemia. Modern prescriptions such as pioglitazone have better therapeutic potential. However, the side effects and financial burden for developing countries have motivated researchers to find alternative natural drugs to compete with hyperglycemia in diabetic patients. This study was conducted to explore the therapeutic potential of selected medicinal plants for treating diabetes as an alternative to allopathic drugs. (Glinus oppositifolius (L.) Aug. DC. is one of the alternative natural ingredients with high flavonoid compounds with hyperglycemia activity. The purpose of this study was to determine the effect of reducing blood sugar levels of ethanol extract of jumpai stem (Glinus oppositifolius (L.) Aug. DC.)) in male Swiss mice that are burdened with sucrose and the effective concentration of blood sugar levels. Methods: The type of research used in this study is pure experimental complete randomized design unidirectional pattern. A total of 25 mice were randomly divided into five groups, namely the negative control group, positive control (acarbose 80 mg/KgBB), sucrose control, and treatment concentration rating of ethanol extract of jumpai stem (Glinus oppositifolius (L.) Aug. DC.), namely 5%; 10%; and 15% orally. Sucrose was given 30 minutes after treatment. Observations were made at 0, 60, 120, and 180 minutes after sucrose was given by taking blood from the tail. Analysis of results using the trapezoidal method (AUC t0- tn) and statistical analysis using Shapiro-Wilk, Levene test, one-way ANOVA, and post-hoc Bonferroni. Results: It has been investigated that treatment of sucrose-induced diabetic mice with ethanol extracts of the stems of the studied medicinal plants showed a significant effect (P <.05) on fasting blood glucose levels (from baseline to normal range) in a manner comparable to that of reference drugs. The tested plant extracts significantly (P <.05) reduced the glucose concentration in the blood of diabetes-induced mice dose-dependently. The results showed that ethanol extract of jumpai stem (Glinus oppositifolius (L.) Aug. DC.) reduced blood sugar levels in sucrose-loaded male Swiss mice. The effective concentration of blood sugar level reduction of ethanol extract of jumpai stem (Glinus oppositifolius (L.) Aug. DC.) is 4%. Conclusion: It can be concluded that the studied medicinal plants have antihyperglycemic activity. The findings of this study support the use of traditional herbal medicine practices for managing diabetes, which may be due to the presence of bioactive phytoconstituents in the plants. Keywords: Diabetes Mellitus, Antihyperglycemic, Jumpai (Glinus oppositifolius (L.) Aug. DC.)